Effects of Nanocellulose, Cationic Starch, Cationic Polyacrylamide, and Unbleached Softwood Kraft Fibers on the Properties of Recycled Cardboard - Jafar Ebrahimpour Kasmani; Ahmad Samariha (BioResources, 2025)
Separate and combined effects of nanocellulose, cationic polyacrylamide, cationic starch, and bleached softwood kraft fibers were evaluated when producing recycled packaging fluting paper. The focus was on enhancing the structural integrity and performance of this paper product, which is essential for packaging applications. Treatments included 10% refined bleached softwood kraft pulp, 5% cellulose nanofibers, 2% cationic starch, and 0.2% cationic polyacrylamide. Combined treatments involved 5% cellulose nanofibers with 2% starch and 5% cellulose nanofibers with 0.2% cationic polyacrylamide. Handsheets with a grammage of 127 g/m² were produced and tested for physical, mechanical, and microscopic properties. Results showed that these additives, either independently or in combination, improved the properties of the paper. The combination of 5% nanocellulose and 0.2% cationic polyacrylamide yielded the highest density and tensile strength, along with the lowest water absorption. This treatment also enhanced critical strengths in the ring crush and corrugated medium tests, making it optimal for packaging paper production. Electron microscopy revealed reduced porosity in handsheets from combined treatments, which may negatively impact water absorption. Further research is needed to optimize these additives while addressing their effects on water absorption.